2018
DOI: 10.3390/jpm8040042
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Promoter Polymorphisms on the Transcriptional Regulation of the Organic Cation Transporter OCT1 (SLC22A1)

Abstract: The organic cation transporter 1 (OCT1, SLC22A1) is strongly expressed in the human liver and facilitates the hepatic uptake of drugs such as morphine, metformin, tropisetron, sumatriptan and fenoterol and of endogenous substances such as thiamine. OCT1 expression is inter-individually highly variable. Here, we analyzed SNPs in the OCT1 promoter concerning their potential contribution to the variability in OCT1 expression. Using electrophoretic mobility shift and luciferase reporter gene assays in HepG2, Hep3B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Despite a median reduction of OCT1 expression by almost 50% in homozygous duplication carriers, the genetic variant could explain less than 10% of the general variability. Taken together with the lack of strong effects of genetic variants in the SLC22A1 promoter (Bokelmann et al, 2018), only minor effects of cis-acting variants could be concluded. Systematic analyses of the genetic component in the variability of OCT1 expression are highly complicated, as multiple sampling of the same individuals or sampling within multiple members of the family are required.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Despite a median reduction of OCT1 expression by almost 50% in homozygous duplication carriers, the genetic variant could explain less than 10% of the general variability. Taken together with the lack of strong effects of genetic variants in the SLC22A1 promoter (Bokelmann et al, 2018), only minor effects of cis-acting variants could be concluded. Systematic analyses of the genetic component in the variability of OCT1 expression are highly complicated, as multiple sampling of the same individuals or sampling within multiple members of the family are required.…”
Section: Discussionmentioning
confidence: 93%
“…The OCT1 mRNA levels differ up to 113-fold and protein levels up to 83fold between individuals (Nies et al, 2009). However, common promoter variants did not significantly affect the SLC22A1 promoter activity or mRNA expression (Bokelmann et al, 2018).…”
Section: Introductionmentioning
confidence: 84%
“…67,68 Other investigators have also found that brominated chemicals can affect the expression level of membrane transcripts. 69,70 Other treatment-related hepatic transcript changes included upregulation of selected SLC transporters, including upregulation of SLC35E3 (a sugar transporter 71 ), SLC4A4 (a sodium bicarbonate transporter 72 ), SLC22A1 (an organic cation transporter 73 ), and/or SLC26A1 (an anion transporter 74 ). Changes in membrane protein transcripts provide evidence that PBDE exposures alter critical membrane transport systems that govern cellular content and function.…”
Section: Discussionmentioning
confidence: 99%
“…Its main function is to transport drugs into hepatocytes for metabolism or to pump drugs into intestinal epithelial cells [23]. The OCT1 transporter encoding gene (SLC22A1) showed signi cant polymorphism [24,25]. A sequencing analysis of 2171 unrelated individuals from 67 world populations reported 29 variants leading to amino acid substitution, which could be divided into 30 haplotype variants consisting of 16 alleles, most of which had signi cant effects on OCT1 transporter activity [26].…”
Section: Introductionmentioning
confidence: 99%